2015
DOI: 10.1016/j.mjafi.2013.12.015
|View full text |Cite
|
Sign up to set email alerts
|

A clinico radiographic study of immediate loading implants in rehabilitation of mandibular ridges

Abstract: Methods: A total of 30 completely edentulous patients male or female, in the age group of 54e78 years (mean age 65 years), wearing conventional complete dentures were selected and randomly divided in to two groups. A total of 60 implants were placed in the interforaminal area of the mental symphysis (two implants per patients) in 30 patients. Two types of attachment systems namely Ball for group-A and Bar for group-B were used and immediate loading done.Implants were evaluated clinically and radiographically a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 21 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…Based on Newcastle‐Ottawa, none of the studies selected showed a high risk of bias (below 6 stars). One study scored seven stars), one study scored eight stars and one study scored nine stars, indicating a low risk of bias. Mostly, the absence of stars was related to lack of additional factors of comparability, and sufficient follow‐up, considered as 5 years (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on Newcastle‐Ottawa, none of the studies selected showed a high risk of bias (below 6 stars). One study scored seven stars), one study scored eight stars and one study scored nine stars, indicating a low risk of bias. Mostly, the absence of stars was related to lack of additional factors of comparability, and sufficient follow‐up, considered as 5 years (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies evaluated marginal bone loss . Despite the slight increase in bone loss associated with use of unsplinted attachment systems, seven studies found no statistically significant difference between the splinted and unsplinted groups.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…An implant length of at least 13 mm was placed, as a minimum acceptable implant length of 10 mm was considered viable by some authors when immediate loading protocol is to be attempted. 52,53 Care was also taken to ensure primary stability of implants before being immediately loaded. The primary stability is a crucial factor that determines the long-term success of dental implants.…”
Section: Discussionmentioning
confidence: 99%